Addressing current challenges in optimization of lipid management following an ACS event: Outcomes of the ACS EuroPath III initiative. Issue 4 (17th February 2023) - Catapano, Alberico L.; De Caterina, Raffaele; Jukema, J. Wouter; Klempfner, Robert; Landmesser, Ulf; Schiele, François; Sionis, Alessandro
Abstract: Background: Low‐density lipoprotein cholesterol (LDL‐C) lowering is key to reduce atherosclerotic disease progression and recurrent events for patients after acute coronary syndrome (ACS). However, LDL‐C management for post‐ACS patients remains challenging in clinical practice. Hypothesis: The ACS EuroPath III project was designed to optimize LDL‐C management in post‐ACS patients by promoting guideline implementation and translating existing evidence into effective actions. Methods: Three surveys targeting cardiologists ( n  = 555), general practitioners (GPs; n  = 445), and patients ( n  = 662) were conducted in Europe, with the aim of capturing information on patient characteristics and treatment during acute phase, discharge and follow‐up. GPs' and patients' opinions on key treatment aspects were also collected. Based on survey results, international experts and clinicians identified areas of improvement and generated prototype solutions. Participants voted to select the most feasible and replicable proposals for co‐development and implementation. Results: Five key areas of improvement were identified: (1) inappropriate treatment prescribed at discharge; (2) lack of lipid guidance in the discharge letter; (3) inadequate lipid‐lowering therapy (LLT) optimization; (4) gaps in guideline knowledge and lack of referral practices for GPs; (5) patients' concerns about lipid management. Proposed solutions for these focus areas included development of a treatment algorithm for the acute phase, a standardized GP discharge letter, an assessment tool for LLT efficacy at follow‐up, an education plan for GPs/patients and a patient engagement discharge kit. The standardized GP discharge letter and treatment algorithm have been selected as the highest priority solutions for development. Conclusion: These initiatives have the potential to improve adherence to guidelines and patient management after ACS. Abstract : The ACS EuroPath III project was designed to optimize lipid management in post‐ACS patients. Following data collection through 3 surveys, 5 key areas for improvement were identified including inappropriate treatment prescribed at discharge, lack of lipid guidance in the discharge letter, inadequate LLT optimization, gaps in guideline knowledge and lack of referral practices for GPs, and patients' concerns about lipid management. Solutions were proposed for each of these issues, with the generation of a treatment algorithm and a standardized patient discharge letter prioritized for early development.